Finanças e aposentadoria: um estudo com servidores federais - Cardoso, Vanessa Cristina de Carvalho (2022)
This study was developed with the objective of understanding the influence of finances and/or financial planning for the retirement decision of civil servants participating in the ‘Re-construção de Um Viver’ course. The course is offered to federal civil servants by the Universidade Federal de Uberlândia, in the city of Uberlândia/MG; as an action to promote health, training and preparation of the server for retirement. The study involved sixteen employees who were former participants of the course and used a quantitative and qualitative approach with an exploratory and descriptive design. With the quantitative approach, we aim to outline the profile and socioeconomic classification of civil servants; as the collection of these data was carried out by a self-administered questionnaire; to the quantitative data we applied statistical, descriptive and socioeconomic analysis. With the qualitative approach, we aim to identify the influence of finances on the retirement decision and also the financial satisfaction of these servers; being used in data collection interviews with semi-structured script; to these qualitative data we applied the technique of thematic content analysis being categorized the following themes and subthemes: 1) Retirement – meanings, good and bad aspects; 2) Preparation – the PPA/UFU, the experience and the reflected opinion and 3) Finance – satisfaction and dissatisfaction. The results of the study demonstrate in the profile of the servers a predominance of the feminine gender, whose social class is in the scope of the middle class; we showed that the meaning of retirement by civil servants is positive, with temporal freedom being pointed out as a good aspect of retirement and the loss of social interaction as bad; preparation for retirement took place through the course and also involved strategies and personal actions; most public servants feel satisfied with their finances and all of them consider financial preparation important, however, few feel financially prepared. We understand that the influence of finances does not directly affect the retirement decision, but is linked to other factors; civil servants see a decrease in income, which makes them postpone retirement, due to being in debt and not having planned in advance for this moment in life. The study revealed the need to train civil servants in the area of financial education, encouraging financial planning for retirement throughout their careers in the public service.